Implication of SARS-CoV-2 Immune Escape Spike Variants on Secondary and Vaccine Breakthrough Infections - Ahmad, Liyana (Frontiers in Immunology, 2021)
COVID-19 pandemic remains an on-going global health and economic threat that has amassed millions of deaths. Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is the etiological agent of this disease and is constantly under evolutionary pressures that drive the modification of its genome which may represent a threat to the efficacy of current COVID-19 vaccines available. This article highlights the pressures that facilitate the rise of new SARS-CoV-2 variants and the key mutations of the viral spike protein – L452R, E484K, N501Y and D614G– that promote immune escape mechanism and warrant a cautionary point for clinical and public health responses in terms of re-infection, vaccine breakthrough infection and therapeutic values.